Multi-stimuli-response programmable soft actuators with site-specific and anisotropic deformation behavior. (October 2021) - Dong, Yue; Wang, Lu; Xia, Neng; Wang, Yu; Wang, Shijie; Yang, Zhengxin; Jin, Dongdong; Du, Xingzhou; Yu, Edwin; Pan, Chengfeng; Liu, Bi-Feng; Zhang, Li
Abstract: Biological systems with the capabilities of multi-stimuli response and delicate structural changes have inspired the design of soft actuators and robots by either creating anisotropic elements within actuators or patterning site-specific elements on layered actuators. However, introducing these two strategies into one soft actuator has not been well investigated. Here, we present a fast and reliable strategy for constructing programmable graphene oxide (GO)/wax actuators to achieve this goal by printing designable wax patterns composed of oriented wax fibrils onto GO paper. The anisotropic behavior of fabricated GO/wax actuators are proved to be related with the orientation of wax fibrils, so wax patterns consisting of wax fibrils with single and multiple orientations are controlled to print onto one and two sides of GO papers to achieve the diversity, complexity and spatial freedom of their structural changes. The GO/wax actuator with black wax exhibits excellent actuating performance stimulated by infrared light, humidity and heat. Printed programmable actuators are further applied as humidity-driven shape-adaptation gripping, heat-driven autonomous crawling robot and light-driven steerable robot. Certainly, we expect more versatile applications can be achieved by rationally designing corresponding actuators. Graphical Abstract: ga1 Highlights: Designable Wax patterns composed of wax fibrils are printed onto GO papers for programmable actuators. The anisotropic behavior of wax fibrils are demonstrated. Integrated anisotropic and site-specific actuations in one actuator system. Autonomous crawling robots and steerable soft robots are achieved.